An investigation of the effect of initial bubble diameter on the bubble trajectory in the flotation column cell using CFD simulation (Rudarsko-geološko-naftni zbornik, 2022)
The effect of initial bubble diameter on the bubble motion pattern in a flotation column has been studied by the twophase computational fluid dynamics (CFD) method. The two-phase simulations have been done using the volume of a fluid (VOF) model in ANSYS® Fluent® software. The computational field was a square cross-section column with a width of 0.1 m and a height of 1 m into which air was interred as a single bubble from the lower part of the column by an internal sparger. An experimental test has been also performed and the simulated results have been validated using the values obtained for the bubble rise velocity. A comparison of the simulation and the experimental results has confirmed that CFD can predict the bubble rise velocity profile and its value in the flotation column less than 5% relative to the experimental values. Then the simulations have been repeated with a 20% decrease and increase in the initial bubble diameter to investigate the effect of bubble diameter on the bubble flow pattern. The investigations have shown that as the bubble diameter increases, the velocity decreases and the bubble rises in a more zigzag direction as a result of two counter-rotating trailing vortices behind the bubble increasing.